Evaluating Performance of Concrete Special Moment Resisting Frames with Different Seismic Coefficients Using Endurance Time Method - Radmanesh, Hadi; Mohammadi, Majid (Salehan Institute of Higher Education, 2018)
This performance-based study was conducted to investigate the effects of seismic coefficients on performance of concrete special moment frames of 5,7, and 10-storey buildings located in Tehran, Iran. The structures are designed three-dimensionally by ETABS 2016 software according to ACI-318-08. Fifteen specimens were designed with different base shears having seismic coefficients of 0.7, 0.85, 1, 1.15, and 1.30 times the proposed value of Iranian Standard 2800, (i.e. decreased by 70 and 85%, and increased by 115 and 130%). Endurance time method (ETA20in series of ET acceleration function) as well as three real earthquake records was employed to evaluate the seismic performance of the modeled structures. The performance of structures was compared by the time of the first plastic hinges formation in beams and columns, the time of entering to nonlinear region and the time of experiencing storey drift of 2% corresponding to the life safety performance level. It was observed that the results of ET records and real records were similar to each other. A procedure was proposed for finding optimum structure with lower weight using ET method through defining efficient ratio (ER) and cost ratio (CR). Based on the results of ER/CR ratio and considering the importance of collapse prevention performance level, optimum structure was a 7-storey structure with lower weight or cost whose seismic coefficient had been reduced by 70%. It was concluded that high safety can not be achieved simply by increasing the seismic coefficient of structures.